Immediate effects of Pilates based therapeutic exercise on postural control of young individuals with non-specific low back pain: A randomized controlled trial. (October 2017) - Lopes, Susana; Correia, Christophe; Félix, Gonçalo; Lopes, Mário; Cruz, Ana; Ribeiro, Fernando
Highlights: A single session of Pilates exercises improved postural sway and dynamic balance in adults with non-specific low back pain. Pilates exercises also induced a clinical improvement of pain in 48.1% of the participants. However future research should investigate if these immediate improvements are maintained. Pilates exercises may be a useful therapeutic tool, used alone or as a complement, in the management of non-specific low back pain. Abstract: Objectives: Low back pain affects the person's ability to keep balance, especially in challenging conditions. The purpose of this study was to determine the immediate effects of Pilates exercises on postural sway and dynamic balance of young individuals with non-specific low back pain. Design: Controlled laboratory design. Settings and main outcome measures: Forty-six participants with non-specific low back pain were randomized to a Pilates (n = 23, 10 males; age: 21.8 ± 3.2 years) and a control group (n = 23, 9 males; age: 22.8 ± 3.6 years). Postural sway was assessed with a force platform and dynamic balance with the Star Excursion Balance Test, before and after the intervention or rest period. To assess postural sway, participants stood still on an unstable surface set on the force plate for 90s, with eyes closed. Intervention: The intervention lasted 20 min and consisted on four Pilates exercises: single leg stretch (level 1), pelvic press (level 1), swimming (level 1) and kneeling opposite arm and leg reach. Results: At baseline, no differences were found between groups. The Pilates group improved in all the postural sway values (area of CoP: 11.5 ± 3.4 to 9.7 ± 2.7 cm 2, p  = 0.002 and CoP velocity: 2.8 ± 0.6 to 2.3 ± 0.5 cm/s, p  < 0.001) and in the Star Excursion Balance Test. Control group only improved in CoP velocity, however, this improvement was significantly inferior compared to the Pilates group. Conclusions: Pilates exercises immediately improved postural sway and dynamic balance in young adults with non-specific low back pain.